The cytotoxic molecule granulysin is capable of inducing either chemotaxis or fugetaxis in dendritic cells depending on maturation: a role for Vδ2+γδ T cells in the modulation of immune response to tumour?. Issue 3 (16th September 2020) - Sparrow, Emma L.; Fowler, Daniel W.; Fenn, Joe; Caron, Jonathan; Copier, John; Dalgleish, Angus G.; Bodman‐Smith, Mark D.
Summary: Release of granulysin by γδ T cells contributes to tumour cell killing. A cytolytic 9000 MW isoform of granulysin kills tumour cells directly, whereas a 15 000 MW precursor has been hypothesized to cause both the maturation and migration of dendritic cell (DC) populations. Recruiting DC to a tumour is beneficial as these cells initiate adaptive immune responses, which contribute to the eradication of malignancies. In this study, V δ 2 + γδ T cells were activated by stimulation of peripheral blood mononuclear cells with zoledronic acid or Bacillus Calmette–Guérin (BCG), or were isolated and cultured with tumour targets. Although a large proportion of resting V δ 2 + γδ T cells expressed 15 000 MW granulysin, 9000 MW granulysin expression was induced only after stimulation with BCG. Increased levels of activation and granulysin secretion were also observed when V δ 2 + γδ T cells were cultured with the human B‐cell lymphoma line Daudi. High concentrations of recombinant 15 000 MW granulysin caused migration and maturation of immature DC, and also initiated fugetaxis in mature DC. Conversely, low concentrations of recombinant 15 000 MW granulysin resulted in migration of mature DC, but not immature DC. Our data therefore support the hypothesis that V δ 2 + γδ T cells can release granulysin, which may modulate recruitment of DC, initiating adaptive immune responses. Abstract : V δ 2 + γδ T cells are capable of the release of two isoforms of granulysin; a cytolytic 9000 MW isoform, which kills tumour cells directly, and a 15 000 MW precursor, which has been hypothesized to cause both the maturation and migration of dendritic cell (DC) populations. Recruiting DC to a tumour is beneficial as these cells initiate adaptive immune responses, contributing to the eradication of malignancies. In this study, we show that high concentrations of recombinant 15 000 MW granulysin cause migration and maturation of immature DC, and can also initiate fugetaxis in mature DC, supporting the hypothesis that granulysin released by V δ 2 + γδ T cells may modulate recruitment of DC, influencing initiation of adaptive immune responses.